2004
DOI: 10.1197/j.aem.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Chief Complaint and Discharge Diagnosis in Emergency Department–based Syndromic Surveillance

Abstract: Objective: Emergency department (ED)-based syndromic surveillance systems are being used by public health departments to monitor for outbreaks of infectious diseases, including bioterrorism; however, few systems have been validated. The authors evaluated a ''drop-in'' syndromic surveillance system by comparing syndrome categorization in the ED with chief complaints and ED discharge diagnoses from medical record review. Methods: A surveillance form was completed for each ED visit at 15 participating Arizona hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 15 publications
(19 reference statements)
2
35
0
Order By: Relevance
“…Our Kappa statistic findings comparing the agreement within categories for Discharge Diagnosis and Operational Code are consistent with the findings of Fleischauer13 and Begier14 despite their focus on syndromes while our work was focused on diagnostic categories. When looking at domestic emergency departments, Fleischauer13 and Begier14 found that there is high variability in agreement values across various syndrome classifications.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our Kappa statistic findings comparing the agreement within categories for Discharge Diagnosis and Operational Code are consistent with the findings of Fleischauer13 and Begier14 despite their focus on syndromes while our work was focused on diagnostic categories. When looking at domestic emergency departments, Fleischauer13 and Begier14 found that there is high variability in agreement values across various syndrome classifications.…”
Section: Discussionsupporting
confidence: 89%
“…However, our high level of agreement for both respiratory and digestive system diseases aligned with the findings of Begier14 who identified chief complaint and discharge data aligned for that system. The low level of agreement between the Other category from the Discharge Diagnosis category and Other from the Operational Code category aligned with our hypothesis that additional effort on coding encounters provided more granularity, as compared to the use of primary discharge diagnosis alone 13. The perfect agreement existing in the diseases of the digestive system may have been due to low number of encounters in this category before recoding (n=152).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This level of agreement is slightly higher than seen in other studies [2-4]. However, over 25% of discharge diagnosis data were missing from the EHR, limiting our comparative analysis.…”
Section: Discussionmentioning
confidence: 58%
“…Fleischauer and others [21] used Kappa statistics to assess agreement between syndromic grouping of the chief complaint on presentation in EDs with discharge diagnoses in patient records. They found moderate agreement overall and recommended that the validity of automated surveillance coding could be improved by including discharge diagnoses.…”
Section: Discussionmentioning
confidence: 99%